INTERDISCIPLINARY REVIEW OF PERI-URBAN AREA TO BUILD A GEOGRAPHY LEARNING EXPERIENCE - Elgar, Elgar Balasa Singkawijaya; Maryani, Enok (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2023)
Interdisciplinary connects disciplines and without changing from other disciplines. Studying peri-urban areas for students requires skills as well as support in learning geography. The purpose of this writing is to review various literature about peri-urban as a form of interdisciplinary analysis learning for students. Literature review is used to identify findings in various literary studies on the scope and topics faced. The results of interdisciplinary studies of peri-urban science of the region are location as well as the dynamics of the use of agricultural land in non-agricultural also the activity of transportation by mobility recycling, demography there is population dynamics in quantity and quality, sociology there is dynamics social life of the community and the economy there is community activity in utilizing resources. The learning experience of the interdisciplinary review is the digestion of the peri-urban area in its spatial visibility as well as the range of its activities and generates a different geographical learning experience.